2016
DOI: 10.1007/s12663-016-0958-7
|View full text |Cite
|
Sign up to set email alerts
|

Re-Assessment of Coronoid as a Graft for Condylar Reconstruction in TMJ Ankylosis Patients: A Prospective Study and Literature Review

Abstract: No donor site morbidity was observed as reported with other autogenous grafts. Satisfactory mouth opening was observed during follow up period with mean mouth opening 37.33 ± 4.20 mm except one case which required graft removal due to postoperative infection. Radiographically moderate amount of resorption of grafted coronoid process was observed in nearly all the cases however satisfactory mandibular function and occlusion was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Gagan Mehta and Shadab Mohammad conducted a study on 20 cases and reported that there did occur resorption of the coronoid in most of the cases. However, that did not change mandibular function and occlusion [34].…”
Section: Coronoid Process Graft (Fig 659b)mentioning
confidence: 78%
“…Gagan Mehta and Shadab Mohammad conducted a study on 20 cases and reported that there did occur resorption of the coronoid in most of the cases. However, that did not change mandibular function and occlusion [34].…”
Section: Coronoid Process Graft (Fig 659b)mentioning
confidence: 78%
“…[19][20][21] In addition, cheek scaring is recognized as the main factor contributing to intermaxillary contracture. 11,14,22,23 Here, we not only reconstructed the unilateral condylar process, but also performed occlusion reconstruction and released the cicatricial contracture on the lower mandible margin. This contributed greatly to maintenance of the morphology and function of the TMJ in both the uninjured side and reconstructed side.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recently, autogenous coronoid process grafts have been recognized as an ideal option for condylar reconstruction, due to the suitable shape and thickness of the coronoid process, its accessibility, and the satisfactory postsurgical results. 914 However, the success of the surgery relies on the accuracy of the deformity diagnosis and the presurgical planning. It is generally agreed that computer-aided design/computer-aided manufacturing (CAD/CAM) can assist in the surgical correction of tissue defects, repositioning of dislocated fragments, and the shaping of bone asymmetry.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Condylar compromise warranting reconstruction can occur following traumatic injuries, infection, tumor resection, radiation necrosis, or prior condylar surgery. 2,3,[6][7][8][9][10][11][12][13] Presentations of the aforementioned may include unilateral or bilateral involvement and, in either case, can cause significant malocclusion with the potential for long-term arthralgia, trismus, and other problems if not appropriately managed.…”
mentioning
confidence: 99%
“…Ankylosis of the mandibular condyle is an unfortunately common pathology most often following trauma or a significant, untreated, chronic infection. 2,3, 10,14 Ankylosis results in bony or fibrous adhesions of the condyle, 14 yielding overall failure of the condyle to promote growth in younger patients and possibly resulting in disfigurement 4 as well as crippling joint function overall. Mandibular tumors may involve the condyle and surrounding soft tissue and include but are not limited to squamous cell carcinoma, osteomas, chondrosarcoma, and multiple myeloma.…”
mentioning
confidence: 99%